(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
The aim of the present work was the study of functional condition of adolescents of gymnasium «Nersisyan» during the examionation period. Mathematical analysis of heart functional factors and hemodinamic exponents changes of pupils showed that the examination stress brings to the tension of Central Nervous system. Changes in the integral factors state the prefominace of the sympathetic part of Nervous system. The results reflect the most strained function of adolesents’ circulatory system during the examination period.